Outcome of visuospatial dysfunction assessment in patients with Parkinson’s disease using mobile application software - Shao, Xu; Wang, Kang; Zhang, Yulian; Zhen, Xueke; Dong, Fen; Tian, Hong; Yu, Yanbing (Frontiers in Aging Neuroscience, 2023)
Background: Visuospatial dysfunction and cognitive impairment are common in Parkinson's disease (PD), draw increasing attention in the current literature. But clinicians still lack rapid, effective and unified cognitive battery for visuospatial assessment. Objective: A new approach was studied to explore the feasibility of using mobile application software (APP) to evaluate visuospatial dysfunction in patients with PD and compare with traditional assessment tools. We aimed to verify the threshold score of the APP for early diagnosis. Materials and Methods: A total of 41 patients with PD underwent assessments using several test modules including Digit Symbol Test (DST), Visual Organization Test (VOT), Facial Recognition Test (FRT), Vocabulary Memory Test (VMT) of this APP, as well as Clock Drawing Test (CDT), Cube Copying Test (CCT)and the Mini-Mental State Examination (MMSE) for comparison. Among the 41 PD patients, 30 individuals were found to have visuospatial dysfunction based on CDT score <5 and CCT score of<18 while the remaining 11 patients served as control. Results: There were statistically significant differences in DST, VOT, FRT scores (all p≤0.001 for group comparisons). DST, VOT, and FRT-1 were significantly correlated with MMSE, CDT and CCT and the correlations were moderate or fairly strong. For visuospatial dysfunction diagnosis, all the areas under curves (AUC) of DST, VOT and FRT-1 were statistically significant (p <0.0001, p =0.0002 and p =0.0002, respectively). The estimates and 95% confidence intervals of AUC were 0.8303 (0.6868, 0.9739), 0.8045 (0.6423, 0.9668), and 0.7833 (0.6344, 0.9322), respectively. Their cut-off points for visuospatial dysfunction were 26, 17, and 19, respectively. After dichotomization by the cut-off points, DST had high sensitivity of 96.67% while VOT and FRT-1 had high specificity of 81.82% and 90.91%. Conclusion: This study demonstrated that visuospatial disorders was highly prevalent in PD patients, and the APP used in study can be a practical clinical screening tool for visuospatial ability assessment with high sensitivity and specificity.